Gene mining: A case study on putative iron-responsive cyanobacterial genetic locus using in silico bioinformatics, ecophysiology and expression-combined approach - El Semary, NA (Bangladesh Journal of Botany, 2014)
Gene mining is an advanced approach used for annotating genetic loci and assigning them a putative function. In that regard, a Phormidium-like cyanobacterium was initially tested positive for its ability to produce iron-chelators. To mine for the putative genetic locus associated with these iron-chelators, a combined bioinformatics, ecophysiological, molecular and expression approach was applied. In order to test for the influence of iron limitation/starvation on the putative gene(s) involved, different levels of iron limitation/starvation were applied and the expression was quantified using real-time PCR. Mild iron limitation induced the expression of this iron-responsive locus at the beginning of iron stress but no detectable levels of expression were found as the stress continued. This possibly indicates the switch off of this putative genetic locus under conditions of extreme iron starvation. This locus is most likely involved in the synthesis of a membrane-associated protein that mediates iron transport or binding across membrane. DOI: http://dx.doi.org/10.3329/bjb.v43i1.19751 Bangladesh J. Bot. 43(1): 79-86, 2014 (June)